The performative resilience of international humanitarian law in a time of discursive amnesia - D'Aspremont, Jean (Zbornik znanstvenih razprav (Pravna fakulteta. 1991), 2025)
This article starts by diagnosing the discursive amnesia that came to surround international humanitarian law in contemporary public discourse in 2023–2025. While violations of IHL have proliferated, the legal categories that render warfare legible - civilian, combatant, proportionality, distinction - have been systematically evacuated from political and media narratives. It is submitted here that this silence is as dangerous as the violations themselves, as it condemns international humanitarian law’s prescriptions to oblivion. The article identifies five plausible causes of this discursive amnesia: intra-norm competition with the legal rules on genocide, complexity in asymmetric conflicts, the narrative monopoly of jus ad bellum discourse, critical discomforts with the colonial and gendered histories of international humanitarian law, and the emergence of zones of incriticability. Against this diagnosis, the article argues that international humanitarian law has lost none of its performative lustre, which can be tapped and mobilized through sustained, institutionally-backed articulation of its core categories. The article concludes with an invitation to mobilize the performativity of international humanitarian law across legal, educational, operational, and communicative registers.
Keywords: diskurz; diskurzivna amnezija; javni diskurz; medijski narativi; mednarodno humanitarno pravo; performativnost prava; razlikovanje ivojskovanje